The Impact of Big Data Analytics Capabilities on Sustainable Performance: an Application to Culinary and Fashion SME’s - Nanang Adie Setyawan; Bagus Yunianto Wibowo; Mellasanti Ayuwardani; Vinda Setya Kartika; Novitasari Eviyanti (Cita Konsultindo Research Center, 2023)
Using the analytical capabilities of Big Data, this research investigates the mechanisms by which sustainable performance helps create sustainable value. The research also looks at how supply chain management capabilities (SCMC) and circular economy practices (CEP) act as mediators in influencing sustainable performance. The focus of this research is micro, small, and medium enterprises (MSMEs) operating in Central Java in the food and fashion industries. This study used purposive sampling method and took 100 samples from the respondent population. Data were collected through questionnaires and then processed through path analysis using SPSS version 25. The results of the path analysis conducted, it can be seen that the Big Data Analytic Capabilities variable has a direct influence on Sustainable Performance through the mediating variables of Supply Chain Management and Circular Economy Practices.